2021
DOI: 10.1039/d1nr01535d
|View full text |Cite
|
Sign up to set email alerts
|

Superior and stable ferroelectric properties of hafnium-zirconium-oxide thin films deposited via atomic layer deposition using cyclopentadienyl-based precursors without annealing

Abstract: The superior and stable ferroelectric properties of HZO films deposited via ALD were demonstrated for the first time without a post-thermal process, which can be applied to ferroelectric devices where process temperature constraints are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…However, employing a higher deposition temperature can produce a high-quality film with low impurity concentration and high density, resulting in low-temperature crystallization. Accordingly, Kim et al demonstrated the benefit of using higher deposition temperatures by depositing HZO films with a cocktail precursor containing CpHf and CpZr . For deposition, cocktail precursors with a molecular ratio of 35:65 for CpHf and CpZr, respectively, were used.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, employing a higher deposition temperature can produce a high-quality film with low impurity concentration and high density, resulting in low-temperature crystallization. Accordingly, Kim et al demonstrated the benefit of using higher deposition temperatures by depositing HZO films with a cocktail precursor containing CpHf and CpZr . For deposition, cocktail precursors with a molecular ratio of 35:65 for CpHf and CpZr, respectively, were used.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
“…Accordingly, Kim et al demonstrated the benefit of using higher deposition temperatures by depositing HZO films with a cocktail precursor containing CpHf and CpZr. 60 For deposition, cocktail precursors with a molecular ratio of 35:65 for CpHf and CpZr, respectively, were used. For adequate vapor pressure, the precursor had to be heated and bubbled.…”
Section: Atomic Layer Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional ferroelectric materials such as Pb­(Zr,Ti)­O 3 (PZT) and P­(VDF-TrFE), hafnium-based ferroelectric films show the advantages of high residual polarization strength ( P r ), high Curie temperature ( T c > 200 °C), high compatibility with CMOS process, good interface performance with semiconductor materials, and high dielectric constant . Ferroelectricity can be observed in the doped HfO 2 film with a thickness of less than 10 nm, which makes it suitable for small-sized devices.…”
Section: Introductionmentioning
confidence: 99%
“…These precursors, however, sometimes have drawbacks such as halide contamination and low stabilities in the case of the halide and alkoxides, respectively. Consequently, heteroleptic precursors including more than one type of ligands such as cyclopentadienyl (Cp)-alkoxides and Cp-alkylamides are developed, to enhance the thermal stability of precursors of the ALD high-k oxides. When ozone is used as the oxygen source, ALD using zirconium and hafnium Cp-alkylamide precursors shows high growth per cycle (GPC), ranging from 0.8 to 0.9 Å per cycle, and the deposited films mostly possessed low levels of nitrogen and carbon contamination. Especially, ZrO 2 and HfO 2 films deposited using CpZr­(N­(Me 2 ) 3 and CpHf­(N­(Me 2 ) 3 precursors (Me = CH 3 ) and ozone have shown improved film density and electrical performance, possibly due to the deposition temperatures being as high as 350 °C.…”
Section: Introductionmentioning
confidence: 99%